2015
DOI: 10.1159/000438518
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Promotes Invasion, Migration and Epithelial-Mesenchymal Transition of Human Endometrial Carcinoma Cell HEC-1A Through AKT and ERK1/2 Signaling

Abstract: Background/Aims: Osteopontin (OPN) is an Extracellular Matrix (ECM) molecule and is involved in many physiologic and pathologic processes, including cell adhesion, angiogenesis and tumor metastasis. OPN is a well-known multifunctional factor involved in various aspects of cancer progression, including endometrial cancer. In this study, we examined the significance of OPN in endometrial cancer. Methods: The proliferation, migration and invasion ability of HEC-1A cells were detected by Cell Counting Kit-8 (CCK-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…Furthermore, the secretory OPN levels of 2 metastatic cell lines, SW620 and HCT116, and 2 non-metastatic cell lines, DLD1 and SW480, were investigated, the OPN level of the SW620 and HCT116 cell lines were found to approximate a concentration of 300 ng per ml [8]. A recent study of uterine endometrial carcinoma showed that exogenous OPN was capable of promoting tumor cells invasion, migration, and epithelial-mesenchymal transition (EMT) [27]. To evaluate the possible roles of extracellular OPN, our team used OPN-specific antibody to block the secreted OPN by HCT116 cells for the purpose of analyzing the influence of autocrine OPN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the secretory OPN levels of 2 metastatic cell lines, SW620 and HCT116, and 2 non-metastatic cell lines, DLD1 and SW480, were investigated, the OPN level of the SW620 and HCT116 cell lines were found to approximate a concentration of 300 ng per ml [8]. A recent study of uterine endometrial carcinoma showed that exogenous OPN was capable of promoting tumor cells invasion, migration, and epithelial-mesenchymal transition (EMT) [27]. To evaluate the possible roles of extracellular OPN, our team used OPN-specific antibody to block the secreted OPN by HCT116 cells for the purpose of analyzing the influence of autocrine OPN.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs promote endothelial cell migration and tube formation by proteolytically remodelling the basement membrane [2, 38]. Among these, MMP-2 and MMP-9 have been emphasized because their type IV collagenase activity is essential during the initial phase of angiogenesis [20, 39].…”
Section: Discussionmentioning
confidence: 99%
“…OPN is a secreted multifunctional glycophosphoprotein that is overexpressed in various tumors and plays important roles in cell adhesion and migration [21-23]. Several experiments have demonstrated that OPN plays a crucial role in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%